CLINICAL EFFICACY OF HERBAL DRUG WITH ANTI-INFLAMMATORY AND IMMUNOSTIMULATING ACTIVITY IN CHILDREN WITH ADENOIDITIS - I. I. Klimova; V. N. Zorina; R. M. Zorina ("Paediatrician" Publishers LLC, 2013)
Aim: to evaluate serum concentrations of cytokines (pro-inflammatory - interleukin 8 (IL8) and tumor necrosis factor α (TNF α); anti-inflammatory - IL 10; immunoregulatory - IL 6), α2-macroglobulin (MG), its immune complexes (MG-IgG) and several other inflammatory markers (α1-antitrypsin and lactoferrin) in healthy children aged from 2 to 12 years old and in patients with chronic adenoidits of the same age group. According to received data - to prove reasonability of usage of herbal drug with anti-inflammatory and immunostimulating effects in a complex treatment of children with adenoiditis. Patients and methods: 22 healthy children (control group) and 62 children with chronic adenoiditis (CA) were examined. Results: it was found that serum concentration of MG, MG-IgG, α1-antitrypsin and IL 10 is significantly higher in children with CA. The level of lactoferrin is also increased. The abovementioned changes in coupled with tendency to decrease of IL 8 concentration in CA suggest that this condition is characterized mainly by compensated immune reactions according to Th2-type. However, certain characteristics of protein and cytokine metabolism in CA contribute to chronization of pathological process, which clinically is manifested by prolonged torpid inflammation. Taking into account special features of CA pathogenesis and in order to increase efficacy of treatment of this disorder an herbal drug with complex action was used. Conclusions: including of the studied drug into the scheme of CA treatment increases efficacy of provided therapy and accelerates temps of convalescence. The drug is safe and can be used for prolonged periods of time.